Description of a new genus and new species of freshwater crab (Crustacea, Decapoda, Potamidae) from Yunnan, China - Yeo, Darren C. J.; Zhou, Xianmin; Ng, Peter K. L. (Zootaxa, 2024)
A new genus and new species of freshwater crab is described from Yunnan Province, China. Proboscimon keeae gen. n., sp. n. belongs to a group of Chinese genera that lack a flagellum on the exopod of the third maxilliped. Of these, it is superficially most similar to Arquatopotamon Chu, Zhou & Sun, 2017 from Yunnan, but is distinguished from it and other genera mainly by the form of its male first pleopod as well as characters of the carapace, thoracic sternum, and male sternopleonal cavity.